Optimal Planning and Operation of CCHP System Considering Renewable Energy Integration and Seawater Desalination. (February 2019) - Chen, Peiyu; Lan, Yu; Wang, Dan; Wang, Weiliang; Liu, Weikang; Chong, Zhiqiang; Wang, Xudong
Abstract: The combined operation of renewable energy and seawater desalination equipment will be the directions of the cleaner freshwater producing technology in the future. A CCHP system that includes wind turbine, photovoltaic, combined heating and power (CHP) and seawater desalination is built in the paper. Based on load characteristics of seawater desalination devices and other critical equipment and characteristics of renewable energy, the optimal planning and operation strategies of CCHP system is discussed by considering economical and environmental benefits, the electric cooling ratio and the capacity of critical equipment are optimized by considering capital cost, operation cost and maintenance cost, energy cost and equivalent carbon tax. Simulation and analysis result verifies the feasibility of the proposed planning and operation strategies that the total cost and CO2 emission reduced.